Solution of equation 4-2(x-5)=x-19 is given below .
Step-by-step explanation:
4-2(x-5)=x-19
Rearrange:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
4-2*(x-5)-(x-19)=0
Step by step solution :
Step 1 :
Equation at the end of step 1 :
(4 - 2 • (x - 5)) - (x - 19) = 0
Step 2 :
Step 3 :
Pulling out like terms :
3.1 Pull out like factors :
33 - 3x = -3 • (x - 11)
Equation at the end of step 3 :
-3 • (x - 11) = 0
Step 4 :
Equations which are never true :
4.1 Solve : -3 = 0
This equation has no solution.
A a non-zero constant never equals zero.
Solving a Single Variable Equation :
4.2 Solve : x-11 = 0
Add 11 to both sides of the equation :
x = 11
One solution was found :
x = 11
Processing ends successfully